Causes of delay in the construction of drinking water and sewer projects in Ecuador (Gaceta Técnica, 2022)
It is common for infrastructure projects to experience delays in their execution, when they occur in the construction of drinking water and sewerage projects, there is a delay in the access and availability of basic water and sanitation services for the population, which is why It is important to know the causes that produce them in order to take actions to reduce them. This article presents the results of an investigation carried out on the delays in the construction of potable water and sewerage systems in Ecuador, the actions taken to correct such delays, and the techniques, and construction planning and control tools used. For this purpose, a survey was conducted based on a questionnaire that required the perception of professionals who work in both public and private institutions in Ecuador, linked to construction activities, preparation of studies or inspection of drinking water projects and sewerage. It was identified that the main cause for the delays in these projects is the deficiency in the studies, the technical modifications and the increases in work quantities, that the term extensions is the measure mainly applied to correct the delays and that the Diagram Gantt Bar is the most widely used planning and control technique.
Keywords: construction delays; drinking water supply; project planning and control; drinking water and sewerage projects